The isocapnic buffering phase and mechanical efficiency: Relationship to cycle time trial performance of short and long duration - Bentley, D. J.; Vleck, V. E.; Millet, G. P. (Canadian Journal of Applied Physiology, 2005)
The purpose of this study was to determine the relationship between the isocapnic buffer (ßisocapnic) and hypocapnic hyperventilation (HHV) phases as well as performance in a short (20-min) and long (90-min) time trial (TT) in trained athletes. In addition, gross (GE, %) and delta (DE, %) efficiency were calculated and the relationship between these variables and the average power output (W) in each TT was determined. Thirteen male endurance athletes (Mean ± SD age 31 ± 6 yrs; body mass 75.6 ± 6.3 kg; height 185 ± 6 cm) completed a continuous incremental test to exhaustion for determination of the ßisocapnic and HHV phases. A second submaximal test was used to determine GE and DE. The average power output (W) was measured in a 20-min and 90-min cycling TT. The ßisocapnic phase (W) was significantly correlated to the average power output (W) in the 20-min TT (r = 0.58; p < 0.05), but not in the 90-min TT (r = 0.28). The HHV phase (W) was not significantly correlated to the average power output in the 20-min or 90-min TT. No significant correlation was found for GE or for DE and performance in the TT. The data from this study shows that ßisocapnic together with HHV is not likely to be a useful indicator of cycle TT performance of 20- to 90-min duration. Furthermore, GE and DE determined from a submaximal incremental stepwise test are not related to cycling TT performance of different duration.